Effect of Proteolytic Treatment on Dyeing of Caseinwith Synthetic Dyes - Dogru, Mehmet; Baysal, Zubeyde; Aytekin, Cetin (Asian Journal of Chemistry, 2010)
The activity of proteolytic enzymes is commonly measured using casein as a substrate. Modified caseinolysis assay was developed with synthetic dyes such as procion red, procion yellow and procion blue for subtilisin carlsberg, protease type XVI, trypsin, chymotrypsin, respectively. Optimum pH, incubation time were determined. KM, Vmax and kcat/KM values were also determined for these enzymes. The results indicate that the effect of all the tested enzymes on the synthetic dye-casein complexes; the most appropriate complex was found to be procion yellow.